Developing AKM Problem-Oriented Websites as Learning Media for Flat Shapes - Iva Wulandari; Siti Inganah; Minatun Nadlifah (Universitas Swadaya Gunung Djati, 2023)
Abstract. This research is motivated by the inability of students to comprehend the concept and correctly answer questions on flat shapes in literacy. This research is a development study with the goal of creating a flat shaped, website oriented learning resource for junior high school class VIII students regarding AKM questions. The ADDIE development model is employed. Interviews, questionnaires for validity and practicality tests, and tests in the form of a pretest and posttest were employed as the data gathering instruments. Ten eighth-grade students from SMPN 13 Malang who participated in the AKM program served as the field trial participants. In order to evaluate the validity, applicability, and efficacy of data collection procedures, tests, questionnaires, and interviews are used. The media validity test yields a percentage of 91.4% (more than 90%), the material validity test yields a percentage of 94% (more than 90%), the practicality percentage is 90.25% (more than 90%), and the Paired t-test yields a significant difference between the pretest and the posttest.Keywords: Development, Website Learning Media, AKM Questions.